Fast Convergence of Regularized Learning in Games - Syrgkanis, Vasilis; Agarwal, Alekh; Luo, Haipeng; Schapire, Robert E. (Advances in Neural Information Processing Systems 28 (NIPS 2015), 2015)
We show that natural classes of regularized learning algorithms with a form of recency bias achieve faster convergence rates to approximate efficiency and to coarse correlated equilibria in multiplayer normal form games. When each player in a game uses an algorithm from our class, their individual regret decays at O(T−3/4), while the sum of utilities converges to an approximate optimum at O(T−1)–an improvement upon the worst case O(T−1/2) rates. We show a black-box reduction for any algorithm in the class to achieve O (T−1/2) rates against an adversary, while maintaining the faster rates against algorithms in the class. Our results extend those of [Rakhlin and Shridharan 2013] and [Daskalakis et al. 2014], who only analyzed two-player zero-sum games for specific algorithms.
Best Paper Award